Does asymptomatic/uncomplicated SARS-CoV-2 infection during pregnancy increase the risk of spontaneous preterm birth? - AY, NADİYE PINAR (My University, 2022)
Objectives: The aim of this study was to analyze the perinatal outcomes of asymptomatic/uncomplicated SARS-CoV-2 infection during pregnancy and the relationship between gestational age at the time of infection and spontaneous preterm birth (PTB). Material and methods: This was a retrospective cohort study. The study population included pregnant women who were 19–45 years old and who had been admitted to a Research and Training Hospital for singleton birth delivery. Women who had contracted SARS-CoV-2 during their pregnancy (n = 102) were compared to those who were not infected (n = 378) for 1 the development of spontaneous PTB and other perinatal outcomes. The factors associated with spontaneous PTB were analyzed through univariate and multivariate methods. Results: Spontaneous PTB developed in 22.5% of the pregnant women with a history of SARS-CoV-2 infection and in 5.3% without a history of the infection (p < 0.001). The multivariate model determined that compared to the non-infected women, the OR of spontaneous PTB among those who had contracted the virus in the first, second, and the third trimesters were 9.13 (p < 0.001), 1.85 (p = 0.292) and 7.09 (p < 0.001), respectively. Pregnancy cholestasis (3.9% vs 0.5%; p = 0.020) and placental abruption (3.9% vs 0.5%; p = 0.040) were significantly higher in cases with a history of SARS-CoV-2 infection compared to the non-infected women. Conclusions: Asymptomatic or uncomplicated SARS-CoV-2 infection during pregnancy increases the risk of spontaneous PTB. This risk is higher particularly among pregnant women who develop the infection in the first and the third trimesters.
Keywords: SARS-CoV-2; COVID-19 pandemic; pregnancy; preterm birth; perinatal outcome